Forced oscillation response of the dynamic surface tension of molten titanium - Zhiyong Yu; Wenjun Li; Xiaowei Dai; Yang Yang; Yangyang Zhao; Boxue Song (PLoS ONE, 2025)
Background This study employed the molecular dynamics simulation method to systematically investigate the dynamic response behavior of the molten titanium liquid-vapor interface under high-frequency (50 GHz) and large-amplitude (5%) transverse mechanical cyclic impact. Methods Based on the theory of driven-damped oscillators, we analyzed the steady-state forced oscillation characteristics of dynamic surface tension. Through frequency analysis, the dependence of the system response on the impact frequency was revealed. And by using the liquid stratification method, we investigated the space-time correlation characteristics of the bulk and surface atomic dynamics. Results This study mainly found that the average value of dynamic surface tension increased by 7% compared to the equilibrium state, confirming that high-frequency mechanical impact has a regulatory effect on surface tension. Meanwhile, the peak and valley of instantaneous fluctuations reached 14% and 5% of the equilibrium state respectively, presenting a significant nonlinear oscillation characteristic. Theoretical analysis indicates that there is a coupling effect between the generalized natural frequency and the damping constant. Experimental observations show that the atomic dynamics behavior of the outermost layer is significantly different from that of the bulk liquid. Conclusion This study has deepened our understanding of the dynamics of the liquid-vapor interface under extreme conditions. It provides new theoretical basis for understanding the multi-scale behavior of liquid metals and has guiding significance for the surface control of high-frequency mechanical impacts and industrial applications.